Take it to the queen : a tale of hope - Nobisso, Josephine; Szegedi, Katalin, 1963- (Westhampton Beach, N.Y. : Gingerbread House, 2008)
Presents an original fable about ungrateful villagers who turn away from their king, his wife, and the prince and bring disaster upon themselves; but when they find themselves desolate, they repent and ask the queen to intervene on their behalf.
3.8
K-3
Keywords: Conduct of life -- Juvenile fiction; Kings and rulers -- Juvenile fiction; Christian life -- Juvenile fiction; Conduct of life -- Fiction; Kings, queens, rulers, etc. -- Fiction; Christian life -- Fiction; Historical fiction; Conduct of life -- Fiction; Kings and rulers -- Fiction; Christian life -- Fiction; Historical fiction